2017
DOI: 10.1038/s41467-017-01305-w
|View full text |Cite
|
Sign up to set email alerts
|

Hyperconnected molecular glass network architectures with exceptional elastic properties

Abstract: Hyperconnected network architectures can endow nanomaterials with remarkable mechanical properties that are fundamentally controlled by designing connectivity into the intrinsic molecular structure. For hybrid organic–inorganic nanomaterials, here we show that by using 1,3,5 silyl benzene precursors, the connectivity of a silicon atom within the network extends beyond its chemical coordination number, resulting in a hyperconnected network with exceptional elastic stiffness, higher than that of fully dense sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(110 citation statements)
references
References 64 publications
6
101
2
1
Order By: Relevance
“…In recent years the field of amorphous materials has welcomed newcomers such as organic glasses (Gujral et al, 2018), optically active molecular amorphous materials (Murawski et al, 2018), two-dimensional amorphous materials (Huang et al, 2012(Huang et al, , 2013 and hybrid organic-inorganic networks, providing even more flexibility in designing their physical properties (Burg et al, 2017).…”
Section: The Amorphous Statementioning
confidence: 99%
“…In recent years the field of amorphous materials has welcomed newcomers such as organic glasses (Gujral et al, 2018), optically active molecular amorphous materials (Murawski et al, 2018), two-dimensional amorphous materials (Huang et al, 2012(Huang et al, , 2013 and hybrid organic-inorganic networks, providing even more flexibility in designing their physical properties (Burg et al, 2017).…”
Section: The Amorphous Statementioning
confidence: 99%
“…The elastic modulus and the hardness of the adhesive layers with varying Zr/GPTMS ratios are shown in Figure . Elastic modulus and hardness are fundamental material's property and are mainly determined by the network connectivity and bond stiffness . Here, the denser and stiffer inorganic molecular networks formed by TPOZ incorporation lead to increases in both elastic modulus and hardness of the adhesive layer.…”
Section: Resultsmentioning
confidence: 99%
“…Bhattarai et al recently reported that the mean atomic coordination, < r >, determines the Young's modulus of SiOCH films, E , expressed as E(italicr>true〈<r>normalctrue〉)3/2, where < r > c is the critical coordination of 2.4 for hydrogenated group IV materials, such as SiOCH, and 4.0 for SiC and SiO 2 . The network connectivity thus determines Young's modulus in proportion to a power law with exponent 1.5 . This may allow the prediction of physical sputtering yields and RIE rates …”
Section: Challengesmentioning
confidence: 99%